Comic Media Improves Female Student Behavior In Facing Menarche - Ni Wayan Suarniti; Erny Astiti, Ni Komang; Dwi Purnamayanti, Ni Made; Novya Dewi, I Gusti Agung Ayu; Wirata, I Nyoman (International Journal of Midwifery and Health Sciences, 2024)
Background: Knowledge about menstruation should have been acquired since elementary school, but in reality it is still rare for elementary schools to provide additional lessons about menstruation. This results in low student behavior in approaching menarche. Purpose: Analyze differences in female students' behavior in facing menarche before and after receiving Health Education through comic media Methods: This research uses a quasi-experimental method, namely by providing information regarding menarche and the practice of preparing for menarche through broadcasting e-comics and distributing comics to read at home. The target is elementary school students in class V and class VI, who have not experienced menarche, are in good health and are willing to be the target of the activity. Location of Service at SDN 26 Pemecutan, Tegal Kertha Village, West Denpasar. The Wilcoxon statistical test was used because the data was not normally distributed. Results: The result is that health education through comic media can improve female students' knowledge, attitudes and practices regarding readiness to face menarche. The output achieved is Comic book product IPR with Number EC00202153064, dated 7 October 2021. Conclusion: there are differences in female students' behavior in dealing with menarche before and after receiving Health Education through comic media